Functional traits of fruits of particular importance for seed dispersers in the tropical dry forest - Acevedo-Quintero, Juan Fernando; Zamora-Abrego, Joan Gastón; Chica-Vargas, Juan Pablo; Mancera-Rodríguez, Néstor Javier (Revista de Biología Tropical, 2023)
Introduction: Frugivory is a pivotal ecological process for the structure and regeneration of forests. Particularly in the tropics, where the diversity of frugivorous animals and plants is high, interspecific relationships are complex generating interaction networks where species play differential functional roles. Objective: To identify which are the most ecologically important plant species in two interaction networks in a Colombian dry forest and to determine which functional traits of the fruits explain this importance. Methods: The plant importance index (PII) was calculated based on the frugivore species (birds and mammals) relevance, in networks structure, with which each plant species interacts. This relevance is directly related to the animal’s potential to be an effective seed disperser. Then, using generalized linear models (GLM), it was evaluated which fruits functional traits (size, color, stratum, type of pulp) explain the PII. Results: Species of the genera Miconia, Ficus, Cecropia, Bursera, Casearia and Trichilia are in the among most important plants. These genera have been previously identified as important resources for frugivores in the tropics. Particularly in this work, we identified that plants with small-size, red and fleshy fruits benefit the best potential seed dispersers. Conclusions: The high PII values variation ​​suggests that the set of frugivore species benefited by each plant species has a differential contribution to the ecological processes derived from seed dispersal. This information is relevant for the species selection with traits that favor the functional forests recovery through ecological restoration programs of threatened ecosystems such as the tropical dry forest (bs-T).